OPTIMIZING CONFISCATION OF CORRUPTION ASSETS THROUGH CIVIL LAW - Zefanya Gloria Tachika Lianta; Amelia Chandra Kartika; Naya Hapsari; Tiara Tiara; Arneta Adelia Santoso; Marcelina Lovely Awaeh (Problematika Hukum, 2022)
For a long time, Indonesia has been facing the complexity of corruption cases. Corruption turns out to be more than just a legal issue. It is also a violation of people's economic and social rights. Poverty, significant social disparities, and overall state losses are also the result of corruption, so Indonesia must always find solutions to rampant corruption. The Follow the Money approach is one of the approaches used in Indonesia to combat corruption today. This approach also uses the main concept of the Corruption Eradication Law (UU PTPK), namely the concept of "state loss recovery" as a legal basis. The return of assets resulting from corruption in the realm of public and civil law is an important part of combating corruption in restorative efforts. Thus, it is expected that every legal source used in Indonesia can optimize the process of asset forfeiture to restore state losses caused by corruption, both in public and civil law.Keywords: Corruption; Corruption Eradication Committee; Confiscation of Assets